1994
DOI: 10.1021/bi00203a013
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of a Peptide Corresponding to T4 Lysozyme Residues 59-81 by NMR and CD Spectroscopy

Abstract: The conformation, in solution, of a peptide corresponding to residues 59-81 from T4 lysozyme [LYS(59-81)] has been determined by 1H NMR and CD spectroscopy. This peptide spans the region corresponding to helix C in the crystal structure of T4 lysozyme. Secondary structure predictions indicated that the peptide would possibly be helical in an aqueous environment, but in a more hydrophobic environment the peptide would certainly adopt a helical conformation. This prediction was confirmed by the far-UV CD and NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 60 publications
12
29
0
Order By: Relevance
“…This implies that either the NMR data are not sufficient to define the relative orientations of sections of the helix, or that the long helix has genuine flexibility. The high degree of curvature observed in most of our structures is not surprising, as this is commonly observed for amphipathic helices in solution (33,34). Analysis of the backbone H-bonds shows that all structures contain a mixture of i,iϩ3, and i,iϩ4 interactions, consistent with 3 10 and ␣-helix, respectively, where the 3 10 helix component consists of approximately 38% of the total backbone H-bonds.…”
Section: Three-dimensional Structure Of Conantokin Peptidessupporting
confidence: 69%
“…This implies that either the NMR data are not sufficient to define the relative orientations of sections of the helix, or that the long helix has genuine flexibility. The high degree of curvature observed in most of our structures is not surprising, as this is commonly observed for amphipathic helices in solution (33,34). Analysis of the backbone H-bonds shows that all structures contain a mixture of i,iϩ3, and i,iϩ4 interactions, consistent with 3 10 and ␣-helix, respectively, where the 3 10 helix component consists of approximately 38% of the total backbone H-bonds.…”
Section: Three-dimensional Structure Of Conantokin Peptidessupporting
confidence: 69%
“…Periodicity is also observed for the HN chemical shifts (Fig. 2D), and this type of periodicity has been attributed to ␣-helix curvature (41,42). The secondary H␣ shifts, which are the most sensitive to secondary structure, appear to be on a gradient decreasing from residues 8 to 28 (Fig.…”
Section: Amylin Adopts An ␣-Helical Structure In the Presence Of Sdsmentioning
confidence: 72%
“…However, in 100% TFE PrP(121-127) adopted a random coil conformation, indicating that this peptide lacks a helical turn propensity. TFE titration offers a good method for analyzing the helical propensity of peptides (Chakrabartty et al, 1993;McLeish et al, 1994Merukta et al, 1990Nelson and Kallenbach, 1986;Satheeshkumar and Jayakumar, 2003). Fezoui and Teplow (2002) observed that the percentage of helical content increased in Ab 1À42 with increased TFE concentration.…”
Section: Resultsmentioning
confidence: 99%